Advances in Microbiology, Infectious Diseases and Public Health Volume 9 (Advances in Microbiology, Infectious Diseases and Public Health, 2018)
This book series focuses on current progress in the broad field of medical microbiology, and covers both basic and applied topics related to the study of microbes, their interactions with human and animals, and emerging issues relevant for public health. Original research and review articles present and discuss multidisciplinary findings and developments on various aspects of microbiology, infectious diseases, and their diagnosis, treatment and prevention. Advances in Microbiology, Infectious Diseases and Public Health is a subseries of Advances in Experimental Medicine and Biology, which has been publishing significant contributions in the field for over 30 years and is indexed in Medline, Scopus, EMBASE, BIOSIS, Biological Abstracts, CSA, Biological Sciences and Living Resources (ASFA-1), and Biological Sciences. 2016 Impact Factor: 1.881.